BK polyomavirus encephalitis in a patient with thrombotic microangiopathy after an allogeneic hematopoietic stem cell transplant. Issue 6 (17th November 2016) - Jun, Jae‐Bum; Choi, Yunsuk; Kim, Hawk; Lee, Sun Ho; Jeong, Joseph; Jung, Jiwon
Abstract: To date, only one case of BK polyomavirus (BKPyV) encephalitis combined with transplant‐associated thrombotic microangiopathy has been reported in an hematopoietic stem cell transplantation (HCT) recipient. We report the case of an HCT recipient who developed thrombotic microangiopathy and subsequent BKPyV encephalitis. She died despite treatment with cidofovir, ciprofloxacin, and intravenous immunoglobulin without improvement in mental status. Early suspicion of BKPyV encephalitis in an HCT recipient presenting with altered mental status and hemorrhagic cystitis is important.